Unravelling the Stability of Nightingale Song Over Time and Space Using Open, Citizen Science and Shared Data - Jäckel, Denise; Mortega, Kim G.; Brockmeyer, Ulrich; Lehmann, Gerlind U. C.; Voigt-Heucke, Silke L. (Frontiers in Ecology and Evolution, 2022)
Open science approaches enable and facilitate the investigation of many scientific questions in bioacoustics, such as studies on evolution and ecology over time and space of song such as vocal dialects. In contrast to previous dialect studies, which mostly focused on songbird species with a small repertoire, here we studied the nightingale (Luscinia megarhynchos), a bird species with a complex and large repertoire. To study dialects on the population level in this species, we used recordings from four datasets: an open museum archive, a citizen science platform, a citizen science project and shared recordings from academic researchers. We conducted the to date largest temporal and geographic dialect study of birdsong including recordings from 1930 to 2019 and from 13 European countries, with a geographical coverage of 2,652 kilometers linear distance. To examine temporal stability and spatial dialects, a catalogue of 1,868 song types of the European nightingale was created. Instead of dialects in the relative frequency of song types, we found the highest degree of stability over time and space in sub-categories of song and in the occurrence of song types over time and space in sub-categories of song and in the occurrence of song types. The second most common nightingale song type within our data occurred over nine decades and across Europe. Two-thirds of all song types occurred not only at the reference site but also in other regions of Europe. In our case study, open and citizen science data proved to be equivalent, and in some cases superior, to data shared by academic researchers from a single working group, while their combination was particularly useful for a bird species with a large repertoire.